O processo criativo de Pierre Boulez em Douze Notations : série, métrica e material musical = The creative process of Pierre Boulez in Douze Notations: series, metrics and musical material - Ferreira, Alberto, 1991- (2018)
Orientadores: Denise Hortência Lopes Garcia, José Augusto Mannis